Cinnamaldehyde modified polyvinyl alcohol antibacterial coating liquid as well as preparation method and application thereof

The cinnamaldehyde modified polyvinyl alcohol antibacterial coating solution prepared by the condensation reaction of cinnamaldehyde and polyvinyl alcohol solves the problem that polyvinyl alcohol packaging materials are susceptible to microbial contamination and the antibacterial film is prone to film breakage, and achieves efficient and safe preparation of antibacterial packaging materials.

CN119708934APending Publication Date: 2025-03-28福建榕升纸业有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900028.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing polyvinyl alcohol packaging materials are susceptible to microbial contamination, and the antibacterial film that uses microcapsules to wrap cinnamaldehyde has problems such as prone to rupture and poor mechanical properties.

Method used

Through the condensation reaction of cinnamaldehyde and polyvinyl alcohol, a cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution is prepared to form a single-material plastic film with antibacterial effect.

Benefits of technology

It realizes packaging materials that are easy to prepare, have excellent antibacterial properties, are safe and easy to use, extends the shelf life of fruits and vegetables agricultural products, reduces production costs, and promotes the sustainable development of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708934A_ABST
    Figure CN119708934A_ABST
Patent Text Reader

Abstract

The invention relates to cinnamyl aldehyde modified polyvinyl alcohol antibacterial coating liquid as well as a preparation method and application thereof. The cinnamyl aldehyde modified polyvinyl alcohol is prepared by condensation reaction of cinnamyl aldehyde and polyvinyl alcohol. The preparation method of the cinnamyl aldehyde modified polyvinyl alcohol antibacterial coating liquid sequentially comprises the following steps: (1) preparing a polyvinyl alcohol aqueous solution; (2) preparing a mixed solution; and (3) preparing the cinnamyl aldehyde modified polyvinyl alcohol antibacterial coating liquid. The invention overcomes the defects that the existing polyvinyl alcohol is easy to be polluted by microorganisms when being used for packaging, and the plastic film prepared by physically blending cinnamyl aldehyde and resin wrapped by microcapsules is easy to break; the cinnamyl aldehyde and polyvinyl alcohol are subjected to condensation reaction to prepare the cinnamyl aldehyde modified polyvinyl alcohol antibacterial coating liquid with cinnamyl aldehyde modified polyvinyl alcohol as a main component, and the cinnamyl aldehyde modified polyvinyl alcohol antibacterial coating liquid has the advantages of being convenient to prepare, excellent in antibacterial performance, safe and convenient to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid and a preparation method and application thereof, and the coating liquid is applied in the field of production of food fresh-keeping packaging materials. Background Art

[0002] In daily life, one of the reasons for the deterioration of fruits and vegetables is the massive reproduction of microorganisms. At present, many fruit and vegetable foods are directly packaged in corrugated boxes, but most of the corrugated boxes themselves have no antibacterial effect and cannot extend the shelf life of fruits and vegetables.

[0003] Polyvinyl alcohol (PVA) is a water-soluble polymer material and a new type of food packaging material with excellent performance. It has good film-forming properties, mechanical properties, thermal stability and gas barrier properties. It has been approved by the US Department of Agriculture for food packaging of meat and poultry products. Therefore, it is selected as a material for degradable packaging film. However, due to the large amount of -OH in PVA, it has high hygroscopicity and poor water resistance. When it is used for food packaging, it is easy to be contaminated by microorganisms such as bacteria and fungi because of the high water absorption of the abundant -OH on the surface of the film.

[0004] Cinnamaldehyde (CIN) comes from cinnamon essential oil. It is a typical active ingredient of natural plant essential oil. It is non-toxic and harmless, and its main volatile component is volatile oil (Lu Xuexue, Tian Hui. Research progress on the active ingredients and pharmacological effects of cinnamon [J]. Zhuang Yao Medicine Research, 2023, (02): 16-20+382.). If it is used in food active packaging, it can also improve its volatility and irritating odor, and reduce the sensory impact on food (Li Qingqing, Liu Guiling, Ren Tian. Research progress on the antibacterial application of cinnamaldehyde in food active packaging [J]. Journal of the Chinese Cereals and Oils Association, 2021, 36 (04): 161-168.). In addition, cinnamaldehyde has no damaging effect on human and other animal cells. The important reason is that human and other animal cells do not have cell walls, and cinnamaldehyde cannot destroy them (Cui Rui. Research on the performance and release law of cinnamaldehyde biodegradable antibacterial active packaging film [D]. Kunming University of Science and Technology).

[0005] Therefore, most of the products on the market now use CIN as an antibacterial agent, and basically adopt the method of physically blending CIN with resin by microcapsules to prepare plastic films. However, this product has many shortcomings: due to the incompatibility of microcapsules and resins, phase separation is prone to occur, making the production and processing of the coating film difficult (easy to break the film); at the same time, the mechanical properties of the film are poor.

[0006] After investigation, it was found that CIN as an additive can react with the polymer matrix of active groups. For example, there have been reports on the research of alcohol-soluble protein film and deacetylated chitosan film (Balaguer MP, Gómezestaca J, Gavara R, et al. Functional properties of bioplastics made from wheat gliadins modified with cinnamaldehyde [J]. J Agric Food Chem, 2011, 59 (12): 6689-6695;

[0007] Higueras L, López-Carballo G, Gavara R, et al. Reversible covalent immobilization of cinnamaldehyde on chitosan films via schiff base formation and their application in active food packaging [J]. Food & Bioprocess Technology, 2015, 8 (3): 526-538). However, there is no detailed report on the modification of PVA using CIN.

[0008] Therefore, it is urgent to provide a cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid that is easy to prepare, has excellent antibacterial properties, is safe and convenient to use, and a preparation method and application thereof. Summary of the invention

[0009] In order to overcome the disadvantage that the existing polyvinyl alcohol packaging is easily contaminated by microorganisms, and the plastic film prepared by physically blending cinnamaldehyde and resin with microcapsules is easy to break, the present invention provides a cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid and a preparation method and application thereof. The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid, whose main component is cinnamaldehyde-modified polyvinyl alcohol, is prepared by condensation reaction of cinnamaldehyde and polyvinyl alcohol. The coating liquid has the advantages of convenient preparation, excellent antibacterial performance, safety and convenient use.

[0010] The technical solution of the present invention is as follows:

[0011] A cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid, the main component of which is cinnamaldehyde-modified polyvinyl alcohol, the molecular formula of which is:

[0012]

[0013] The cinnamaldehyde-modified polyvinyl alcohol is prepared by condensation reaction of cinnamaldehyde and polyvinyl alcohol.

[0014] The synthesis mechanism of cinnamaldehyde-modified polyvinyl alcohol:

[0015] Polyvinyl alcohol has many -OH groups, which can theoretically produce a condensation reaction with the aldehyde group on cinnamaldehyde. The reaction formula is shown below:

[0016]

[0017] It can be seen from the formula that aldehyde reacts with carbonyl in a nucleophilic addition reaction under acidic conditions, which will affect the distribution of cinnamaldehyde in the membrane matrix and the microstructure of the membrane. The physical properties and microstructure of the membrane are closely related to the interaction between the active substance and the polymer matrix (Yang Xiangxin. Aldehyde condensation reaction and its application in organic synthesis [J]. Journal of Shandong Textile Institute, 1991, (04): 65-73. DOI: 10.13306 / j.1006-9798.1991.04.013). Different from the existing physical blending method of directly adding cinnamaldehyde (CIN) to polyvinyl alcohol (PVA) (which is prone to the phenomenon of separation of the two substances), this case adds cinnamaldehyde to the polyvinyl alcohol matrix through mixing to chemically modify the polyvinyl alcohol membrane. Through the condensation reaction, cinnamaldehyde is grafted and polymerized into polyvinyl alcohol, creating a new antibacterial polymer to provide more scientific basis for food storage. This new type of cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid can be directly coated on the surface of fruit and vegetable packaging (such as corrugated paper boxes, etc.) to form a single-material plastic film with antibacterial effect, giving it excellent antibacterial effect, thereby effectively extending the shelf life of fruit and vegetable agricultural products, greatly saving production costs, and achieving sustainable development of resources.

[0018] The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid comprises the following steps performed in sequence:

[0019] (1) adding polyvinyl alcohol powder to water and stirring in a water bath at 93-97° C. until completely dissolved to obtain a polyvinyl alcohol aqueous solution having a weight-to-volume ratio of 0.035-0.045 g / ml;

[0020] (2) adding cinnamaldehyde at a volume ratio of 1-3% to the polyvinyl alcohol aqueous solution obtained in step (1), stirring evenly to obtain a mixed solution;

[0021] (3) adjusting the pH value of the mixed solution obtained in step (2) to 1.8-2.2 with concentrated hydrochloric acid, and then stirring the mixture at 38-42° C. for at least 2 hours to obtain the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution.

[0022] The preparation method of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid has simple steps and is easy to operate. The concentrated hydrochloric acid in step (3) has strong oxidizing properties, and its H+ in the solution can react with -OH in PVA to make the C on PVA in an unsaturated state, thereby being able to undergo a condensation reaction with C=0 on CIN.

[0023] In step (2), the mixing ratio of cinnamaldehyde and polyvinyl alcohol aqueous solution is 1% by volume.

[0024] The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid obtained by the preferred mixing reaction ratio of cinnamaldehyde and polyvinyl alcohol has the best mechanical properties and antibacterial properties after film formation.

[0025] The weight-to-volume ratio of the polyvinyl alcohol aqueous solution in step (1) is 0.04 g / ml.

[0026] The viscosity of PVA at 0.04 g / ml is moderate, and it is easy to fully contact with CIN during the solution reaction, which is more conducive to the occurrence of the reaction.

[0027] When in use, the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is coated on a packaging cardboard or a packaging bag, and is naturally air-dried to form a film.

[0028] The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is simple to use and easy to operate.

[0029] The packaging paperboard is corrugated paperboard, and the packaging bag is a nylon packaging bag or a polyester packaging bag.

[0030] The preferred packaging paperboard and packaging bag are common and easily available, and have good film-forming effect and excellent antibacterial performance after being coated with the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1) The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid of the present application adopts the condensation reaction of cinnamaldehyde and polyvinyl alcohol to prepare the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid whose main component is cinnamaldehyde-modified polyvinyl alcohol, which has the advantages of convenient preparation, excellent antibacterial performance, safety and convenient use;

[0033] 2) The preparation method of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid has simple steps and is easy to operate;

[0034] 3) The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid obtained by the preferred mixing reaction ratio of cinnamaldehyde and polyvinyl alcohol has the best mechanical properties and antibacterial properties after film formation;

[0035] 4) The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is simple to use and easy to operate;

[0036] 5) The preferred packaging paperboard and packaging bag are common and easily available, and have good film-forming effect and excellent antibacterial performance after being coated with the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The infrared spectrum of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid and its preparation method, and the applied cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid;

[0038] Figure 2 It is a schematic diagram of the molecular structure of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid and its preparation method, and the applied cinnamaldehyde;

[0039] Figure 3 It is a schematic diagram of the molecular structure of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid and its preparation method and the polyvinyl alcohol used in the present invention;

[0040] Figure 4 The invention discloses a DSC (differential scanning calorimetry) spectrum of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid and a preparation method thereof, and an applied cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid;

[0041] Figure 5 The invention discloses the antibacterial performance test results of the cinnamaldehyde modified polyvinyl alcohol antibacterial coating liquid and its preparation method and application. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments.

[0043] Example 1

[0044] The molecular formula of cinnamaldehyde-modified polyvinyl alcohol, the main component of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid described in the present invention, is:

[0045]

[0046] The cinnamaldehyde-modified polyvinyl alcohol is prepared by condensation reaction of cinnamaldehyde and polyvinyl alcohol.

[0047] The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid comprises the following steps performed in sequence:

[0048] (1) adding polyvinyl alcohol powder to water and stirring in a 95° C. water bath until completely dissolved to obtain a polyvinyl alcohol aqueous solution with a weight-to-volume ratio of 0.04 g / ml;

[0049] (2) adding cinnamaldehyde at a volume ratio of 1% to the polyvinyl alcohol aqueous solution obtained in step (1), stirring evenly to obtain a mixed solution;

[0050] (3) The pH value of the mixed solution obtained in step (2) is adjusted to 2 with concentrated hydrochloric acid, and then stirred for reaction at 40° C. for 2 h to obtain the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution.

[0051] When in use, the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is coated on a packaging cardboard or a packaging bag, and is naturally air-dried to form a film.

[0052] The packaging paperboard is corrugated paperboard, and the packaging bag is a nylon packaging bag or a polyester packaging bag.

[0053] Example 2

[0054] The molecular formula of cinnamaldehyde-modified polyvinyl alcohol, the main component of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid described in the present invention, is:

[0055]

[0056] The cinnamaldehyde-modified polyvinyl alcohol is prepared by condensation reaction of cinnamaldehyde and polyvinyl alcohol.

[0057] The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid comprises the following steps performed in sequence:

[0058] (1) adding polyvinyl alcohol powder to water and stirring in a 93° C. water bath until completely dissolved to obtain a polyvinyl alcohol aqueous solution with a weight-to-volume ratio of 0.045 g / ml;

[0059] (2) adding cinnamaldehyde at a volume ratio of 2% to the polyvinyl alcohol aqueous solution obtained in step (1), stirring evenly to obtain a mixed solution;

[0060] (3) The pH value of the mixed solution obtained in step (2) was adjusted to 1.8 with concentrated hydrochloric acid, and then stirred for reaction at 42° C. for 2.5 h to obtain the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution.

[0061] When in use, the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is coated on a packaging cardboard or a packaging bag, and is naturally air-dried to form a film.

[0062] The packaging paperboard is corrugated paperboard, and the packaging bag is a nylon packaging bag or a polyester packaging bag.

[0063] Example 3

[0064] The molecular formula of cinnamaldehyde-modified polyvinyl alcohol, the main component of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid described in the present invention, is:

[0065]

[0066] The cinnamaldehyde-modified polyvinyl alcohol is prepared by condensation reaction of cinnamaldehyde and polyvinyl alcohol.

[0067] The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid comprises the following steps performed in sequence:

[0068] (1) adding polyvinyl alcohol powder to water and stirring in a 97° C. water bath until completely dissolved to obtain a polyvinyl alcohol aqueous solution with a weight-to-volume ratio of 0.035 g / ml;

[0069] (2) adding cinnamaldehyde at a volume ratio of 3% to the polyvinyl alcohol aqueous solution obtained in step (1), stirring evenly to obtain a mixed solution;

[0070] (3) The pH value of the mixed solution obtained in step (2) is adjusted to 2.2 with concentrated hydrochloric acid, and then stirred for reaction at 38° C. for 3 hours to obtain the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution.

[0071] When in use, the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is coated on a packaging cardboard or a packaging bag, and is naturally air-dried to form a film.

[0072] The packaging paperboard is corrugated paperboard, and the packaging bag is a nylon packaging bag or a polyester packaging bag.

[0073] Raw materials and equipment information involved in each embodiment:

[0074] Polyvinyl alcohol (PVA): Zhonglian Reagent 1799 (Tianjin Zhonglian Chemical Reagent Co., Ltd.)

[0075] Cinnamaldehyde (CIN): Purity: 98%, Ron's reagent

[0076] Concentrated hydrochloric acid (HCL): (Guangdong Xinchengyuan Technology Co., Ltd.)

[0077] Beef extract peptone: 250g / bottle, Zhonglian Reagent (Tianjin Zhonglian Chemical Reagent Co., Ltd.)

[0078] Escherichia coli strains, second generation slant strains: (Shanghai Luwei Technology Co., Ltd.)

[0079] Beaker: 50ml, 500ml, 1000ml

[0080] Digital constant temperature water bath (Changzhou Yuexin Instrument Manufacturing Co., Ltd.)

[0081] Digital display magnetic stirrer (Youke Experimental Equipment Co., Ltd.)

[0082] Glass plate: 20cm*20cm

[0083] Petri dish: 60mm

[0084] Oxford cup: 8*6*10mm

[0085] Electric constant temperature blast drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.)

[0086] Refrigerator: Haier

[0087] Fourier transform infrared spectrometer (Thermo Fisher Nicolet)

[0088] Differential Scanning Calorimeter DSC (PerkinELmer)

[0089] Intelligent tensioner: Model: XCWCP-CD (Jinan Languang Electromechanical Technology Co., Ltd.)

[0090] Thickness gauge: Model: CHY-CB (Jinan Languang Electromechanical Technology Co., Ltd.)

[0091] Photoelectric haze meter: Model: WGW photoelectric haze meter (Shanghai Yidian Physical Optical Instrument Co., Ltd.).

[0092] Experimental data:

[0093] Make sample mixed films for testing:

[0094] After the above-mentioned Examples 1-3 were allowed to stand at room temperature for a period of time until the bubbles completely overflowed, the corresponding cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquids were taken and formed into films on glass plates of 20 cm×20 cm by a casting method, and dried in a constant temperature forced air drying oven at 40°C for 48 hours. After that, the film was carefully peeled off with a knife, and then dried and balanced in a constant temperature forced air dryer at 40°C for about 24 hours before use, that is, 1% PVA-CIN mixed film, 2% PVA-CIN mixed film and 3% PVA-CIN mixed film were obtained respectively.

[0095] Polyvinyl alcohol (PVA) film was used as the blank control group.

[0096] 1. Product verification experiment

[0097] (I) Infrared spectrum detection

[0098] Detection method:

[0099] The 1% PVA-CIN mixed film and the PVA film were analyzed by Fourier transform infrared spectrometer.

[0100] Before testing, place the film in an oven to fully dry, then cut a small piece and place it on the instrument for analysis.

[0101] Analysis of cinnamaldehyde CIN was performed as a control: KBr was fully dried under the infrared lamp on the workbench, and after removing the moisture, KBr was pressed into a tablet. Then a small amount of cinnamaldehyde was dripped on the tablet with a dropper, and then an infrared scan was performed with a scanning range of 400-4000cm -1(Reference: Gao Yi, Huang Tao, Zhang Lu. Research on the progress of infrared spectroscopy technology in forensic science [J]. Optoelectronics Laser, 2024, 35(03): 327-336. DOI: 10.16136 / j.joel.2024.03.0723.).

[0102] Test results such as Figure 1 shown.

[0103] Depend on Figure 1 The infrared spectrum of PVA clearly shows that PVA has a high concentration of 3000-3500cm -1 There is an absorption peak at Figure 3 It can be seen that polyvinyl alcohol molecules contain a large amount of -OH, so it can be inferred that the peak is generated by the large amount of hydroxyl -OH contained in polyvinyl alcohol. -1 and 1414.6cm -1 The absorption peaks are caused by the bending vibration of CH and the stretching vibration of CO bonds in PVA respectively.

[0104] In the CIN infrared spectrum, 1626.1 cm -1 and 1678.6cm -1 Peaks appear, combined with the molecular structure diagram of cinnamaldehyde ( Figure 2 ) analysis can infer that 1626.1cm -1 is the stretching vibration absorption peak of the unsaturated benzene ring, and 1678.6cm -1 It is the stretching vibration peak of the C=O bond of the aldehyde group present in CIN.

[0105] In general, comparing the three curves, we can observe that there are many similar characteristic peaks in the infrared spectrum curves of PVA and PVA-CIN, which can be inferred to be caused by the low amount of added cinnamaldehyde (CIN). However, a careful comparison of the two curves still shows that PVA-CIN has a peak at 2852.8cm -1 There is a ratio of PVA at 2854.2cm -1 The obvious peak at 2852.8 cm -1 The stretching vibration peak at has shifted. The reason for the shift may be that there is a hydrogen bond between PVA and CIN, which causes the stretching vibration peak to shift.

[0106] From the condensation reaction formula of polyvinyl alcohol and cinnamaldehyde, it can be seen that the two react to form a cyclic ether bond, and in the infrared spectrum curve of the PVA-CIN mixed film, 1047.7 cm -1Peaks appear on the left and right, which can be inferred that PVA and CIN have a mixed reaction to form a COC cyclic ether bond, resulting in the appearance of a new absorption peak. The above experimental results can prove that polyvinyl alcohol and cinnamaldehyde have successfully undergone a condensation reaction.

[0107] (II) DSC thermodynamic properties test

[0108] Detection method:

[0109] ①Preparation process before the test:

[0110] 1) Sample preparation: Cut a small piece from each of the sample films (1% PVA-CIN mixed film and PVA film) as the sample film and place it flat on the bottom of the sample plate (the sample mass is 5-10 mg).

[0111] 2) Then use a film tool to gently press and seal the sample in the dish.

[0112] 3) Special attention should be paid to keep the sample clean during the sample preparation process and not contaminated by other conditions. The outer wall of the crucible should not be contaminated by the sample.

[0113] 4) Before use, check whether the furnace is clean. If there is dirt, use a glass brush to gently sweep it or a hair dryer to blow it. (Be careful not to touch the thermocouple in the middle of the sample holder) (Reference: Jiang Hao, Sun Zhijing, Zhang Yanbo, et al. Rapid detection of the main material components of degradable plastics by infrared and differential scanning calorimetry [J]. Plastics Industry, 2023, 51(03): 114-120.)

[0114] ②Formal test steps:

[0115] 1) Sample preparation: Cut a small piece of each sample film (1% PVA-CIN mixed film and PVA film) and put it into a crucible and weigh it on a balance. The mass is 5.6 mg. Then cover the pot with a lid and seal it with a lid press. Then put it on the left sensor of the main furnace and cover it with the furnace cover.

[0116] 2) Open the main valve of the nitrogen cylinder, confirm that the output pressure is 0.14Mpa, and open the dry gas flow valve.

[0117] 3) Turn on the power switch of the refrigeration machine and the power switch of the differential scanning calorimeter DSC (PerkinELmer) to wait for the instrument to start self-test. The green indicator light on the front of the instrument indicates that the self-test is complete.

[0118] 4) Turn on the computer, click the Pyris software on the desktop and select the online button in the software. Double-click the "Pyris Manager" icon on the computer desktop and click the "DiamondDSC" start button on the active window to complete the connection.

[0119] 5) Click the "Control" drop-down menu to find "Go to Standby Temperature". You can start the experiment or calibration in about fifteen minutes. Set the program's heating temperature to 30-350℃, the heating rate to 10℃ / min, and the insulation time to 1 minute.

[0120] After the experiment is completed, if you have no opinion on the results, you can click "ACCEPT" to save. Repeat this operation for other sample membranes.

[0121] The results are as follows Figure 4 shown.

[0122] DSC is used to study the crystallization behavior of the film, determine the crystallization temperature Tc, crystallinity θ, melting point Tm and other temperature crystallization kinetic parameters, glass transition temperature Tg. It is also used to study the mixed reaction of PVA and CIN, and determine the reaction temperature, reaction temperature range, reaction heat, reaction kinetic parameters, etc.

[0123] Depend on Figure 4 It can be clearly seen that the melting enthalpy of the PVA film is higher than that of the 1% PVA-CIN film (the higher the melting enthalpy, the higher the crystallinity of the material). This may be because CIN reacts with PVA, causing PVA to lose some -OH, even if the number of its hydrogen bonds is reduced, resulting in a decrease in the crystallinity of the material. And CIN may contain other impurities, causing the melting enthalpy of the 1% PVA-CIN mixed film to be lower than that of the PVA film. The change in crystallinity is also to prove that a condensation reaction occurred between CIN and PVA, producing a new polymer material, rather than a simple physical mixture of CIN and PVA.

[0124] (III) Film mechanical properties testing

[0125] Detection method:

[0126] ① The test should be based on GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for thin plastics and sheets" (reference Cui Weixin, Wang Kejian. Mechanical properties test methods and standards for plastic packaging films [J]. Plastic Packaging, 2020, 30(03): 44-47+3.); Measure the size of PVA film, 1% PVA-CIN mixed film, 2% PVA-CIN mixed film and 3% PVA-CIN mixed film on the workbench with a ruler, and cut 3 strips of each sample according to the length (L) of 150mm and the width (d) of 15mm;

[0127] ② According to GB / T 6672-2001 "Determination of Thickness of Plastic Film and Sheet", the cut samples are placed on the thickness gauge in turn for measurement. The thickness of the sample is measured at any four points of the test section, and the arithmetic mean is taken, accurate to 0.001mm, as the average thickness;

[0128] ③Then open the intelligent tensile tester and select the tensile strength and elongation test. First set the parameters and input the average thickness of the sample tested by the thickness gauge;

[0129] ④ Start the instrument, pay attention to adjust the distance between the upper and lower clamps, and press the "Stop" button in time to stop the descent when the distance is less than 15mm; clamp the sample so that its center line is aligned with the center line of the upper and lower clamps;

[0130] ⑤ Press the "Test" button to start the instrument and put it into standby mode. After confirming that the parameters are correct, press the "Test" button again to start the experiment;

[0131] ⑥ Repeat the above steps to carry out experimental measurements on the remaining samples;

[0132] Calculation formula: ①σ=(P / b)*h, σ: tensile strength, MPa; b: sample width, mm; h: sample thickness, mm;

[0133] ②E=(ΔLb / L0)*100, E: elongation of the specimen at the maximum load, %; ΔLb: elongation within the gauge length L0 at the maximum load; L0:

[0134] The measuring gauge length, mm.

[0135] The breaking load, tensile strength and elongation at the maximum load of each sample were obtained, and the average value was calculated. The results are shown in Table 1 below:

[0136] Table 1 Determination of tensile properties of films

[0137]

[0138] Conclusion: The breaking load and tensile strength of PVA film are obviously higher than those of PVA-CIN mixed films with CIN added. It is speculated that this may be due to the condensation reaction between PVA and CIN, which leads to the loss of -OH, that is, the number of hydrogen bonds is reduced, so that the tensile strength and breaking load of PVA-CIN film are lower than those of PVA film.

[0139] It can also be seen from Table 1 that the elongation of the PVA film at the maximum load is higher than that of the PVA-CIN mixed film. The reason is speculated to be that the reaction when PVA and CIN are mixed produces a discontinuous structure, which becomes the starting point of the film breakage, causing the film to break prematurely. Therefore, its elongation E / % at the maximum load decreases (Liu Yong, Huang Shujin, Yang Yanchuan, et al. Preparation of cinnamaldehyde / polyvinyl alcohol film and study on the preservation of cucumber acid [J]. Packaging and Food Machinery, 2021, 39(02): 12-17.).

[0140] (IV) Film haze detection

[0141] Detection method:

[0142] ① Connect the power supply of the photoelectric haze meter to a 220V AC power supply, start the instrument and let it preheat for about half an hour.

[0143] ② After preheating, pull the handle of the instrument closer to you. When the light source is stable and the displayed numbers no longer change, you can start testing.

[0144] 1. Measure light transmittance (handle in the closed position):

[0145] ① First, calibrate "0": find the blackboard, use the blackboard to block the integrating sphere entrance window, and adjust the "0" potentiometer until the reading is "0".

[0146] ② Next, calibrate "100": After calibrating "0", take out the blackboard and adjust the "100" potentiometer until the reading is "100". (Calibrate "0" and "100" repeatedly until the reading is stable.)

[0147] ③ Test: Place a piece of sample film cut out for testing and the data obtained is the transmittance (%). Repeat the test three times for each sample film, test four samples, and take the arithmetic mean of the transmittance as the transmittance (%) of each sample film.

[0148] 2. Measure the haze (handle is far away from the body):

[0149] ①Agree to calibrate "0" first: the handle is far away from itself, there should be no sample in the sample chamber, and adjust the "0" potentiometer to read "0".

[0150] ②Calibration "100": With the handle in the closed position, place the sample film in the sample chamber and adjust the calibration "100" potentiometer until the reading is "100". (Calibration "0" and "100" should be repeated several times until the reading is stable.)

[0151] ③ Test: After placing each sample film, make sure that when the potentiometer reads "100", push the handle away from itself, and the measured data is the haze (%). Repeat the measurement three times for each sample film, measure four samples, and take the arithmetic average of their haze as the haze (%) of each sample film.

[0152] The results are shown in Table 2:

[0153] Table 2 Transmittance and haze measurement

[0154]

[0155] Transmittance indicates the light transmission ability of the film, and haze indicates the degree of turbidity and unclearness inside the transparent / translucent material (Qiao Mengxia, Xu Wenzong, Qin Zhongqiong. Research on film forming process and performance [J]. Anhui Chemical Industry, 2022, 48(02): 71-73+77.). In reality, haze and transmittance are two important parameter indicators for the preparation of packaging materials. The higher the transmittance (i.e. transparency), the better, and the lower the haze, the better.

[0156] ① From the transmittance table in Table 2, it is easy to see that the transmittance of the PVA film is 91.2%, which is not much different from the transmittance of the PVA-CIN mixed film after adding different concentrations of CIN (86.4%, 88.8%, and 88.2%). From the perspective of transmittance, the performance of the two films is not much different. In general, although the difference is not big, the transmittance of the PVA-CIN mixture with the addition of CIN will be lower, indicating that the addition of CIN will affect the transmittance of the film. It is speculated that this may be due to the new crystal structure generated by the mixed reaction of CIN and PVA, which has a certain light-blocking property. However, because the amount of CIN added is not large, the change in the crystal structure is not large, so there is not much difference in the transmittance values.

[0157] ② From the haze table in Table 2, it can be seen that the haze of each PVA-CIN mixed film with CIN added is 36.6%, 13.3%, and 14.2%, which is still very different from the haze of the PVA film of 0.58%. In the experiment, the amount of CIN added to our mixed film was not large, but the haze changed greatly, indicating that PVA only needs to react with a small amount of CIN to have a significant effect on the haze of the film, causing it to increase significantly. It can be speculated that this may be because the reaction with CIN destroys the crystallinity of PVA, which increases the haze index of each PVA-CIN mixed film. In addition, each PVA-CIN mixed film contains a mixture of PVA and PVA-CIN. Due to the different materials, the scattering and absorption of light cause the haze to decrease (Wang Sining, Huang Zhen, Ru Xiaofei, et al. Preparation and performance characterization of PVA / UiO-66 composite film [J]. Plastics Industry, 2021, 49(01): 121-125+153.);

[0158] ③Therefore, it can be seen that the changes in haze transmittance and haze of the PVA-CIN mixed film are caused by the condensation reaction of CIN and PVA destroying the crystallinity of PVA.

[0159] 2. Product antibacterial effect test

[0160] Detection method:

[0161] ① Weigh 6.6 g of beef extract peptone and dissolve it in deionized water, and sterilize it at a high temperature of 121°C;

[0162] ② Prepare four culture dishes, pour the sterilized beef extract peptone liquid into the culture dishes, and put them in the refrigerator to cool to make culture medium;

[0163] ③ Cool for one day, and take out the beef extract peptone in the four culture dishes when they have all formed lumps;

[0164] ④ After taking it out, place an Oxford cup in the middle of the culture medium and then drip a small amount of PVA membrane liquid into the center of the Oxford cup, and then inject a small amount of E. coli liquid into the far end of the culture medium with a syringe (first inoculate the second generation slant strain of E. coli into the liquid culture medium to obtain the E. coli liquid); the other three culture media are dripped with the cinnamaldehyde modified polyvinyl alcohol antibacterial coating liquid of each embodiment instead of the PVA membrane liquid, and the other operations are the same;

[0165] ⑤Put the four culture media in the refrigerator, take them out after two days, and observe the reproduction of E. coli in the culture media.

[0166] The results are as follows Figure 5 As shown, from left to right are: the experimental results of adding PVA film liquid, cinnamaldehyde modified polyvinyl alcohol antibacterial coating liquid (1% PVA-CIN) of Example 1, cinnamaldehyde modified polyvinyl alcohol antibacterial coating liquid (2% PVA-CIN) of Example 2 and cinnamaldehyde modified polyvinyl alcohol antibacterial coating liquid (3% PVA-CIN) of Example 3; wherein, the circle marked is the antibacterial circle, and the strength of the antibacterial effect can be judged according to the size of the antibacterial circle.

[0167] Depend on Figure 5 It can be seen that:

[0168] ① The growth rate of E. coli in the culture dish with PVA membrane solution added was much faster than that in the other three dishes;

[0169] ② On the culture dish to which the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid (1% PVA-CIN) of Example 1 was added, it can be clearly seen that E. coli did not multiply around the dripping point, and an obvious antibacterial circle (circled area) was formed. The two on the right did not show obvious antibacterial circles, but it can also be clearly observed that there was almost no E. coli multiplication around the dripping point;

[0170] ③ The antibacterial effect of the antibacterial coating liquid (2% PVA-CIN) modified with cinnamaldehyde in Example 2 and the antibacterial coating liquid (3% PVA-CIN) modified with cinnamaldehyde in Example 3 is not as good as that of the antibacterial coating liquid (1% PVA-CIN) modified with cinnamaldehyde in Example 1. The reason may be that: due to the large amount of CIN added, the -CHO with antibacterial properties in CIN reacts more fully with the -OH of PVA, causing some antibacterial components of CIN to lose their effect, but the overall film liquid still has a certain antibacterial property. Therefore, we can guess that the new structural cyclic ether bond generated by the reaction of PVA and CIN may also have a certain antibacterial property. In the antibacterial coating liquid (1% PVA-CIN) modified with cinnamaldehyde in Example 1, the amount of CIN participating in the reaction is small, so the amount of -CHO antibacterial components that do not participate in the reaction is larger than that of the other two embodiments, and the cyclic ether bond generated by PVA-CIN may also have a certain antibacterial property. Therefore, the antibacterial effect of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution (1% PVA-CIN) in Example 1 is the best.

[0171] ④ In general, the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid (PVA-CIN) has certain antibacterial properties, while the PVA film liquid does not have antibacterial properties. Therefore, we can conclude that the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid (PVA-CIN) generated by the condensation reaction of polyvinyl alcohol (PVA) and cinnamaldehyde (CIN) has antibacterial properties, so the film made from it also has certain antibacterial properties.

[0172] 3. Experimental conclusion:

[0173] (1) Through the above infrared spectrum and DSC thermodynamic property tests, it can be determined that a condensation reaction occurred between PVA and CIN, which changed the melting enthalpy of the original PVA and generated a new structure (PVA-CIN mixed film, whose main component is cinnamaldehyde-modified polyvinyl alcohol);

[0174] (2) The experiment found that the physical properties of PVA film and PVA-CIN mixed film are different. The tensile strength of PVA-CIN film is lower than that of PVA film. Although there is no obvious difference in light transmittance, the light transmittance of PVA film is better. In terms of haze, the haze of PVA-CIN film is higher than that of PVA film. These also prove that CIN was successfully used to modify PVA in this case.

[0175] (3) The antibacterial experiment shows that the antibacterial coating liquid modified with cinnamaldehyde (PVA-CIN mixed solution) exhibits obvious antibacterial properties against Escherichia coli, so the corresponding PVA-CIN film also has certain antibacterial properties; and the antibacterial effect of the antibacterial coating liquid modified with cinnamaldehyde (1% PVA-CIN) in Example 1 is the best.

Claims

1. A cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid, characterized in that: The molecular formula of cinnamaldehyde-modified polyvinyl alcohol, the main component of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid, is:

2. The cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid according to claim 1, characterized in that: The cinnamaldehyde-modified polyvinyl alcohol is prepared by condensation reaction of cinnamaldehyde and polyvinyl alcohol.

3. The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid according to claim 1 or 2, characterized in that: The steps are as follows: (1) adding polyvinyl alcohol powder to water and stirring in a water bath at 93-97° C. until completely dissolved to obtain a polyvinyl alcohol aqueous solution having a weight-to-volume ratio of 0.035-0.045 g / ml; (2) adding cinnamaldehyde at a volume ratio of 1-3% to the polyvinyl alcohol aqueous solution obtained in step (1), stirring evenly to obtain a mixed solution; (3) adjusting the pH value of the mixed solution obtained in step (2) to 1.8-2.2 with concentrated hydrochloric acid, and then stirring the mixture at 38-42° C. for at least 2 hours to obtain the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating solution.

4. The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid according to claim 3, characterized in that: In step (2), the mixing ratio of cinnamaldehyde and polyvinyl alcohol aqueous solution is 1% by volume.

5. The method for preparing the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid according to claim 3, characterized in that: The weight-to-volume ratio of the polyvinyl alcohol aqueous solution in step (1) is 0.04 g / ml.

6. The use of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid according to claim 1 or 2, characterized in that: When in use, the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid is coated on a packaging cardboard or a packaging bag, and is naturally air-dried to form a film.

7. The use of the cinnamaldehyde-modified polyvinyl alcohol antibacterial coating liquid according to claim 6, characterized in that: The packaging paperboard is corrugated paperboard, and the packaging bag is a nylon packaging bag or a polyester packaging bag.